2010
DOI: 10.4103/0975-1483.66798
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Self-Medication Practices Among Médical, Pharmacy, Health Science Students in Gondar University, Ethiopia

Abstract: The study was aimed at assessing the magnitude and factors of self-medication among medical, pharmacy, and health science students of GCMHS (Gondar College of Medicine and Health Sciences). A cross-sectional study with two-month illness recall was conducted. A Questionnaire consisting of demographic questions and questions on illnesses in the last two months prior to the interview and treatment strategies was prepared and administered to the 414 students, selected as the sample population, from the GCMHS stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

84
277
13
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(378 citation statements)
references
References 5 publications
(8 reference statements)
84
277
13
4
Order By: Relevance
“…The illnesses for which students were practicing self-medication were fever & chills (62.5%) followed by pain, headache, cough and common cold. Our results are similar to the study conducted by Abay SN et al inEthiopia [12]. The drugs which were frequently used for self-medication in our study were Analgesics (81.2%) followed by Anti-pyretics(67.6%) and Anti-inflammatory (41.0%); these were the drugs which were used in high frequency; moreover, a study in karachi 6 also showed similar results.…”
Section: Discussionsupporting
confidence: 81%
“…The illnesses for which students were practicing self-medication were fever & chills (62.5%) followed by pain, headache, cough and common cold. Our results are similar to the study conducted by Abay SN et al inEthiopia [12]. The drugs which were frequently used for self-medication in our study were Analgesics (81.2%) followed by Anti-pyretics(67.6%) and Anti-inflammatory (41.0%); these were the drugs which were used in high frequency; moreover, a study in karachi 6 also showed similar results.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies have reported prevalence and pattern of self-medication in medical students with varying results. 10,11 Our results suggest a high prevalence (82%) of selfmedication in our students which is somewhat higher than reported by Zafar et al who studied self medication in medical and non medical students and found no significant difference between the two groups 9 and lower than reported by Badiger et al reporting 92% prevalence in a study of 200 students. 12 The most important reason for higher trend of self medication is easy availability of all categories of medicines-OTC, prescriptions only or even schedule X drugs (Narcotics) without prescription to consumers in India.…”
Section: 3contrasting
confidence: 55%
“…In another study done in Ethiopia, of 82 respondents, antipyretics 46.3% and analgesics 24.4% were again the most common drugs used in self-care. [13] In our study it was found out that the most common reasons for self-medication were similar past experience 40(54.8%), mildness of infection 22(30.1%)and long waiting line in the OPD 11 (15.1%). This is similar to a previous study which also shows previous experience 32.7% and minor nature of the illness 23.2% [16] as the common reasons for self-medication.…”
Section: Discussionmentioning
confidence: 83%
“…[12] In another study done in Ethiopia, 82 (38.5%) practiced self-medication. [13] Prevalence of selfmedication was 41.6% in a study done in two Brazilian Universities. [14] It is also noted that a high level of education and professional status are predictive factors for self-medication.…”
Section: Discussionmentioning
confidence: 99%